Penggunaan Strategi Mind Mapping Untuk Meningkatkan Hasil Belajar Siswa Pada Pelajaran Alquran Hadis Di Madrasah Aliyah Nurul Huda Kabupaten Sukabumi - Nurafifah, Siti Salmah; Agustina, Lina; Syawali, Alwi Muhammad (Universitas Pakuan, 2025)
THE USE OF MIND MAPPING STRATEGY TO IMPROVE STUDENT LEARNING OUTCOMES IN THE LESSON OF AL-QURAN HADIS AT MADRASAH ALIYAH NURUL HUDA SUKABUMI CITY This study aims to examine the effectiveness of the use of Mind Mapping strategies in improving student learning outcomes on the material “Responsibility Toward Family and Society” in Al-Qur'an Hadith subjects in class XI MA Nurul Huda. This study used the method of classroom action research (PTK) which was carried out in two cycles, each cycle consisting of the stages of planning, implementation, observation, and reflection. Data were collected through tests, observation, and documentation. The results showed a significant increase in student learning outcomes. In the first cycle, the average student score was 68%, with 45% of students reaching the Minimum Completion Criteria (KKM), while in the second cycle, the average score increased to 80%, with all students (100%) reaching the KKM. In addition, students' learning motivation also increased from 68% in the first cycle to 76% in the second cycle. The application of Mind Mapping strategy proved effective in improving students' cognitive learning outcomes, as it helped them understand the material in a more structured and visual way. This research contributes to the development of more interactive and effective learning methods, especially in subjects that require understanding complex concepts.